Development of a Molecular Imprinting-Based Surface Plasmon Resonance Biosensor for Rapid and Sensitive Detection of Staphylococcus aureus Alpha Hemolysin From Human Serum - Andersson, Tilde; Bläckberg, Anna; Lood, Rolf; Ertürk Bergdahl, Gizem (Frontiers in Cellular and Infection Microbiology, 2020)
S. aureus is a common infectious agent in e.g. sepsis, associated with both high mortality rates and severe long-term effects. The cytolytic protein alpha-hemolysin has in several murine models repeatedly, as well as in clinical isolates from human, been shown to enhance the virulence of S. aureus. Combined with an unhindered spread of multi drug-resistant strains, this has triggered research into novel anti virulence (i.e. anti alpha-hemolysin) drugs. Their functionality will depend on our ability to identify infections that might be alleviated by such. We therefore saw a need for detection methods that could identify individuals suffering from S. aureus infections where alpha-hemolysin was a major determinant. Molecular imprinted polymers were subsequently prepared on gold coated sensor chips. Used in combination with a surface plasmon resonance biosensor, alpha-hemolysin could subsequently therethrough be quantified from septic blood samples (n= 9), without pre-culturing of the infectious agent. The biosensor recognized alpha-hemolysin with high affinity (KD=2.75 x 10-7 M) and demonstrated a statistically significant difference (p<0.0001) between the alpha-hemolysin response and potential sample contaminants. The detection scheme proved equally good, or better, when compared to antibody-based detection methods. This novel detection scheme constitutes a more rapid, economical, and user-friendly alternative to many methods currently in use. Heightening both reproducibility and sensitivity, molecular imprinting in combination with SPR-technology could be a versatile new tool in clinical- and research-settings alike.